Tahapan dan Strategi dalam Mengakuisisi Perusahaan, Studi Kasus: Akuisisi Hikmah Grafika oleh PT Salmand - Supendi, Arif (Jurnal Surya, 2023)
This acquisition can have a positive impact on the creative industry as a whole. However, the process of integrating and merging companies is also not free from challenges. Combining company culture, operational systems, and work teams requires good planning and coordination to be implemented successfully. The activity method for the acquisition of Hikmah Graphics by PT Salmand consists of 2 major activities, namely a transition program that lasts for 1 year which is supported by the application of main management principles, namely realistic planning, proper organizing, agile actuating, real-time monitoring, and strong control. The acquisition strategy of Hikmah Graphics by PT Salmand using a 9 series transition program method supported by the application of good management principles, using the canvas business model as a program approach, has succeeded in bringing Hikmah Graphics Barokah into a stable and strong company, and ready to carry out expansion or business expansion.